Contact System Activation on Endothelial Cells - de Maat, Steven; de Groot, Philip G.; Maas, Coen (Seminars in Thrombosis and Hemostasis, 2014)
When the contact system assembles and activates on negatively charged surface materials, plasma coagulation rapidly follows. This mechanism is redundant for hemostasis but mediates pathological thrombus formation, as was reported in a multitude of in vivo studies. The epidemiological data are presently scarce to firmly support a role for the contact system in human thrombotic disease, while its physiological function and mode of activation remains mysterious. Besides its role in blood coagulation in vitro, the contact system is responsible for the production of bradykinin. This inflammatory peptide is involved in episodes of pathological tissue swelling in (hereditary) angioedema, but potentially also in the physiological regulation of vascular permeability. A body of evidence indicates that contact system factors are recruited to the surface of activated endothelial cells, where proteins that are locally released can activate them. Furthermore, clinical and biochemical studies indicate that plasmin, the effector enzyme of the fibrinolytic system, can evoke contact system activation. This auxiliary role for plasmin may so far not have been fully appreciated in pathophysiology. To conclude this review, we propose a complementary model for contact system activation on the endothelial cell surface that is initiated by plasmin activity.
Keywords: factor XII; bradykinin; endothelial cells; plasmin; angioedema